Intericonicity in Disguise in Madame Yevonde’s Goddesses series and Cindy Sherman’s History Portraits/Old Masters - Julie MORÈRE (E-REA)
As one of the world’s woman pioneers of colour photography, Yevonde Cumbers Middleton, known as Madame Yevonde, British society photographer, has recently seen her inventive work shift from neglect to international appraisal. Many of Yevonde’s contemporary and exuberant studio portraits have a unique timelessness and modernity to them, in the sense that issues of gender and identity which she dealt with years ago have since found new expression in the work of various artists such as American photographer Cindy Sherman. In her 1935 Goddesses series, Yevonde photographed society beauties dressed as Greek and Roman goddesses and icons. In Sherman’s History Portraits/Old Masters series, pure fun is at work when she outrageously poses in various costumes and elaborate settings, explicitly referring to the artworks of famous European Masters. As they appropriate previous works of art circulating between the European and the American art worlds, are Yevonde and Sherman irreverently saying that myth, civilization and history can be chopped up and freshly reconstituted to express various representations of the feminine subverting the male gaze, regardless of geographical and cultural differences? This paper will argue that both women artists have chosen to pay homage to the past and the way it can be rejuvenated through perpetual recycling and iconic transfers.